Cinética da recristalização e evolução da textura em aço inoxidável ferrítico 430 estabilizado com nióbio, laminado a frio e submetido a recozimentos isotérmicos - Camila Magalhães Gonçalves (2015)
Ferritic stainless steels stabilized with Nb have more refined grains and a recrystallization process more homogeneous than with those steels which are not stabilized. However, in its industrial processing, specifically in hot rolling and annealing, it is usual to have an intermediate annealing treatment before cold rolling stage, in order to obtain a more homogeneous microstructure. Aiming to optimize the stamping and welding properties in steels with Nb, and considering a cost re reduction by eliminating of the intermediary annealing process, a ferritic stainless steel AISI 430 stabilized with Nb was subjected to hot and cold rolling and annealing processing about 80% thickness reduction and an annealing at temperatures of 650ºC, 700ºC, 750ºC and 800ºC, starting from two initial conditions after hot rolling: with and without annealing. The recrystallizing volume fraction was obtained from the softening volume fraction as function of annealing temperature and from Vickers microhardness tests and also via quantitative metallography according to the JMAK model, the recrystallized fraction as a function of annealing time. Texture interpretation was made by scanning electron microscopy and electron back-scattering diffraction (EBSD). The expected results aimed at comparability of direct and indirect measurement of the volume fraction recrystallized methods of ferritic stainless steel. Innovative methods via quantitative metallography and via EBSD, slightly used nowadays, can serve as tools for metallographic analyzes and thus be applied in other cases confidently and quickly.